Virulence Determinants and Antimicrobial Profiles of Pasteurella multocida Isolated from Cattle and Humans in Egypt - Mohamed Sabry Abd Elraheam Elsayed; Samah Mahmoud Eldsouky; Tamer Roshdy; Lamia Said; Nahed Thabet; Tamer Allam; A. B. Abeer Mohammed; Ghada M. Nasr; Mohamed S. M. Basiouny; Behairy A. Akl; Maha M. Nader; Al Shaimaa Hasan; et al. (MDPI AG, 2021)
Pasteurella multocida is a Gram-negative bacterium that causes drastic infections in cattle and humans. In this study, 55 isolates were recovered from 115 nasal swabs from apparently healthy and diseased cattle and humans in Minufiya and Qalyubia, Egypt. These isolates were confirmed by kmt1 existence, and molecular classification of the capsular types showed that types B, D, and E represented 23/55 (41.8%), 21/55 (38.1%), and 11/55 (20.0%), respectively. The isolates were screened for five virulence genes with hgbA, hgbB, and ptfA detected in 28/55 (50.9%), 30/55 (54.5%), and 25/55 (45.5%), respectively. We detected 17 capsular and virulence gene combinations with a discriminatory power (DI) of 0.9286; the most prevalent profiles were dcbF type D and dcbF type D, hgbA, hgbB, and ptfA, which represented 8/55 (14.5%) each. These strains exhibited high ranges of multiple antimicrobial resistance indices; the lowest resistances were against chloramphenicol, ciprofloxacin, amoxicillin/clavulanic acid, and levofloxacin. The macrolide-lincosamide-streptogramin B methylase gene erm(Q), with erm(42) encoding MLSB monomethyltransferase, mph(E) encoding a macrolide efflux pump, and msr(E) encoding macrolide-inactivating phosphotransferase were present. The class 1 and 2 integrons and extended-spectrum β-lactamase genes intl1, intl2, blaCTX-M, blaCTX-M-1, and blaTEM were detected. It is obvious to state that co-occurrence of resistance genes resulted in multiple drug-resistant phenotypes. The identified isolates were virulent, genetically diverse, and resistant to antimicrobials, highlighting the potential risk to livestock and humans.